THE ORCHID GENUS LUISIA IN INDONESIA - SULISTIARINI, DIAH (REINWARDTIA, 1988)
Nine species and one new variety of the genus Luisia are recognized in Indonesia. The newly proposed variety is L. zollingeri Rchb. f. var. iati-petala ( J. J. S. ) Sulistiarini. Complete descriptions, key to all species based on morphological characters as well as lists of specimens examined are presented.